Oxygen isotope ratios of plant available phosphate in lowland tropical forest soils. (September 2015) - Gross, A.; Turner, B.L.; Wright, S.J.; Tanner, E.V.J.; Reichstein, M.; Weiner, T.; Angert, A.
Abstract: Phosphorus (P) cycles rapidly in lowland tropical forest soils, but the process have been proven difficult to quantify. Recently it was demonstrated that valuable data on soil P transformations can be derived from the natural abundance of stable oxygen isotopes in phosphate (δ 18 OP ). Here, we measured the δ 18 OP of soils that had received long-term nutrient additions (P, nitrogen, and potassium) or litter manipulations in lowland tropical forest in Panama and performed controlled incubations of fresh soils amended with a single pulse of P. To detect whether δ 18 OP values measured in the incubations apply also for soils in the field, we examined the δ 18 OP values after rewetting dry soils. In the incubations, resin-P δ 18 OP values converged to ∼3.5‰ above the expected isotopic equilibrium with soil water. This contrasts with extra-tropical soils in which the δ 18 OP of resin-P matches the expected equilibrium with soil water. Identical above-equilibrium resin-P δ 18 OP values were also found in field soils that did not receive P additions or extra litter. We suggest that the 3.5‰ above-equilibrium δ 18 OP values reflect a steady state between microbial uptake of phosphate (which enriches the remaining phosphate with the heavier isotopologues) and the release of isotopically equilibrated cell internal phosphate back to the soil. We also found that soil nutrient status affected the microbial turnover rate because in soils that had received chronic P addition, the original δ 18 OP signature of the fertilizer was preserved for at least eight weeks, indicating that the off-equilibrium δ 18 OP values produced during microbial phosphate turnover was not imprinted in these soils. Overall, our results demonstrate that ongoing microbial turnover of phosphate mediates its biological availability in lowland tropical soils. Highlights: We investigated the cycling of phosphorus (P) in low land tropical forest soils. We measured phosphate oxygen isotopes in long-term nutrient addition experiment. Our results contrasted with data from extra-tropical soils. Phosphate was rapidly turned-over by the soil microbial biomass. The microbial turnover rate was affected by the soil nutrient status.